Toxicity of Fixed Oils, Essential Oils and Isolated Chemicals to Hetorhabditis amazonensis and Steinernema rarum - Alixelhe Pacheco Damascena; Luis Moreira de Araujo Junior; Luiza Akemi Gonçalves Tamashiro; Dirceu Pratissoli (Stresses)
Non-target organisms are not well studied. The objective of this work was to evaluate the effect of seven essential oils, two fixed oils, d-limonene and eugenol on the mortality, behavior and infectivity of entomopathogenic nematodes (ENPs). The oils were diluted at 1% (v/v) in water with Tween® 80 PS at 0.05% (v/v), and water with Tween® alone was used as the control treatment. In the mortality test, 2 mL of solution containing 50 µL of the nematode suspension, 20 µL of oil/compounds solution isolated with Tween 80, and 1930 µL of water were placed in plastic containers. After four days, the number of dead juveniles was counted. In the bioassay of the behavior of the EPNs, the frequency of lateral body beats of the infective juveniles in liquid medium was analyzed after exposure to the solutions. In the infectivity test, after contact of the EPNs with oils and essential oil chemical compounds, the juveniles were washed and applied to second-instar Spodoptera eridania larvae. All oils and isolated compounds caused mortality in H. amazonensis and S. rarum, with Ocimum canum and the isolated compound eugenol showing the highest efficacy against H. amazonensis and O. canum, Eucalyptus citriodora, Zingiber officinale, Salvia sclarea and the isolated compound eugenol being the most effective against S. rarum. There was a reduction in the number of lateral beats of H. amazonensis and S. rarum for all treatments, with the exception of Cymbopogon winterianus in H. amazonensis and Annona muricata in S. rarum. The infectivity of H. amazonenis and S. rarum on S. eridania was reduced when exposed to the solutions, with the exception of the isolated compound d-limonene in both species, soursop for H. amazonenis and rosemary for S. rarum, which were classified as non-toxic to the species tested. The results obtained in this study may be useful for the choice of oils and essential oil chemical compounds with potential use in integrated pest management programs.